Models of Historical Memory and past Representation of Vilnius University in the 19th-20th Centuries - Alfredas Bumblauskas (Lietuvos Istorijos Studijos)
The article aims at presenting the topic of Vilnius University in different ideologically and politically conditioned models of historical memory of the 19th and 20th centuries. The analysis is based on Jorn Rüsen's theory of historical culture. The article focuses on the representational forms of Vilnius University of the past times, such as anniversaries (1828, 1929, 1979, 2004), monuments, commemoration galleries, naming of the courtyards and halls of the University, commemorating both the said anniversaries and marking other occasions, as sources of historical memory. During different periods of development - be it the Russian period (1795-1832), the Polish period (1919-1939), the Lithuanian period (1939-1940, 1941-1943) or the Soviet period (1940-1941, 1944-1990) - Vilnius University became the arena for the dominance of nationalistic, authoritarian, and totalitarian ideologies. Hence it is worthwhile to adjust the historiographic images that fail to deliberate the significance of these factors to the historical memories, fail to embrace the conflicts of the memories, and portray the past of Vilnius University merely from a perspective of a single nationalistic historical consciousness.